Improving the Quality of Thematic Learning Using Video-Based Media in Class II SDN Banyumanik 01 Semarang - Erra May Hilda (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Media is an important component in improving the quality of learning. The purpose of this research is to improve the quality of thematic learning using video media. This research is a classroom action research (PTK) which is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 28 students of class II SDN Banyumanik 01 Semarang. The research instruments were observation sheets, learning test results and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The findings of this study are the use of instructional video media can improve the quality of students' thematic learning on the theme of my daily tasks in class II SDN Banyumanik 01 Semarang. The results showed that the percentage of student learning activities in cycle I 64.11% increased in cycle II to 90.62% and the percentage of students who completed the learning outcomes in cycle I 36.4% increased in cycle II to 95.5%.